Cross-Cultural Pragmatics: An Investigation into Speech Act Realization on The Ship - Limbong, Sunarlia; Palayukan, Novianty; Chandra, Ade; Jayanti, Retno Dwi; Riwu, Willyam Raimond (Universitas Cokroaminoto Palopo, 2025)
This study, titled